2019
DOI: 10.2147/cmar.s202465
|View full text |Cite
|
Sign up to set email alerts
|

<p>Neutrophils infiltration and its correlation with human papillomavirus status in the oral squamous cell carcinoma</p>

Abstract: Purpose: One of the cardinal etiological factors for oral squamous cell carcinoma (OSCC) is Human papillomavirus (HPV). Neutrophils were potential targets of immune therapy for patients with OSCC. The objective of this study was to determine if neutrophils density and HPV status can be used to define a high-risk category of patients in OSCC and to investigate the possible relationship between them. Patients and methods: We performed immunohistochemistry to probe neutrophils i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 50 publications
3
20
0
Order By: Relevance
“…However, similar data have been reported for OSCC [24], although this form of cancer rarely harbours oncogenic HPV [25]. Here, Li et al, observed increased abundance of CD15+ neutrophils in HPV-negative compared to HPV-positive OSCC, as well as finding that high levels of neutrophils correlated with poor 5-year survival, increased lymph node metastasis and were an independent prognostic factor for OSCC [24]. Using The Cancer Genome Atlas (TCGA) data set Chen et al, also found a higher neutrophil genetic imprint for HPV-negative compared to HPV-positive head and neck cancer [26].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…However, similar data have been reported for OSCC [24], although this form of cancer rarely harbours oncogenic HPV [25]. Here, Li et al, observed increased abundance of CD15+ neutrophils in HPV-negative compared to HPV-positive OSCC, as well as finding that high levels of neutrophils correlated with poor 5-year survival, increased lymph node metastasis and were an independent prognostic factor for OSCC [24]. Using The Cancer Genome Atlas (TCGA) data set Chen et al, also found a higher neutrophil genetic imprint for HPV-negative compared to HPV-positive head and neck cancer [26].…”
Section: Discussionsupporting
confidence: 88%
“…However, the chemokine profiles detected using these MCTS directly correlated with the profiles observed for other HPV-positive/negative cell lines in our previous 2D study [13], providing some evidence that these phenomena is not cell line specific but may be a general occurrence for HPV status. In support of this, analysis of the Gene Expression Omnibus (GEO) and TCGA databases showed significantly elevated levels of CXCL8 in HPV-negative compared to HPV-positive tumours [24], consistent with our in vitro 3D model data. In addition to CXCL8, increased abundance of other neutrophil-specific chemokines such as CXCL1, CXCL5 and CXCL6 is likely, as evidenced by our previous cytokine array analysis [13], and this may further skew the imbalance in leukocyte recruitment in favour of preferential neutrophil recruitment.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Experimental and epidemiological evidence indicate an association between chronic inflammation [39,40] and PMN infiltration [25] with cancer prognosis. In addition, high risk HPV infections are closely related with other malignancies, in particular oropharyngeal cancer, where inflammation and high PMN infiltration negatively correlate with patient survival [41,42]. Therefore, novel approaches aimed at modulating PMN actions to control HPV-cancers are of wide interest.…”
Section: Discussionmentioning
confidence: 99%
“…As interferons have been shown to have anti-tumoral capacity ( 114 ) and to prime anti-tumor phenotype of neutrophils ( 8 , 10 , 115 ), this phenomenon should be further exploited. Overexpression of HPV proteins in OSCC cells is also associated with an impaired neutrophil infiltration to the tumor, possibly due to the downregulated expression of IL-8 ( 116 ). While recently a comprehensive single cell RNA sequencing study investigated the differences between intratumoral immune cells isolated from HPV + and HPV – HNC [large differences between B-cells, myeloid cells and conventional CD4 + T-cells, rare differences between regulatory CD4 + T-cells and CD8 + T-cells] ( 117 ), there is to the best of our knowledge no study investigating the influence of HPV status on oPMN phenotype and function.…”
Section: Oral Cancer and Microbiome Shiftmentioning
confidence: 99%